2019
DOI: 10.1016/j.bbmt.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Intestinal Microbiota by Broad-Spectrum Antibiotic Use Correlates with the Occurrence of Intestinal Graft-versus-Host Disease

Abstract: Patients undergoing hematopoietic stem cell transplantation (HSCT) frequently receive empiric antibiotics during the neutropenic period before engraftment. Several recent studies have shown that anaerobes in the intestine are important mediators of intestinal homeostasis, and that commensal bacteria can be potent modulators of the severity of acute graft-versus-host disease (aGVHD). However, the relationships among the type of antibiotic used during the neutropenic period, changes in the intestinal microbiota,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 35 publications
2
35
0
1
Order By: Relevance
“…21,23,25,26 However, the relevant microbiota found to be related to aGVHD was not consistent among different transplant centers. 5,15,22,[25][26][27][28] It may be interpreted that gut microbiota are impacted by many factors, such as antibiotics, conditioning, diet, and geographic environment, 11,15,[29][30][31] and our previous studies have demonstrated such phenomena. 11 The present study demonstrates that the microbiota negatively (eg, Lachnospiraceae and Peptostreptococcaceae) or positively (eg, Enterobacteriaceae) correlate with aGVHD occurrence.…”
Section: Discussionmentioning
confidence: 79%
“…21,23,25,26 However, the relevant microbiota found to be related to aGVHD was not consistent among different transplant centers. 5,15,22,[25][26][27][28] It may be interpreted that gut microbiota are impacted by many factors, such as antibiotics, conditioning, diet, and geographic environment, 11,15,[29][30][31] and our previous studies have demonstrated such phenomena. 11 The present study demonstrates that the microbiota negatively (eg, Lachnospiraceae and Peptostreptococcaceae) or positively (eg, Enterobacteriaceae) correlate with aGVHD occurrence.…”
Section: Discussionmentioning
confidence: 79%
“…In a mouse allo-HSCT model, clindamycin administration was associated with AIC decrease and more severe GvHD, while re-administration of AIC increased its levels in the gut and improved survival. 93 Additionally, Lee et al 94 compared patients who did not require any systemic antibiotic treatment during the transplantation course with those who received cefepime and those who were treated with carbapenem antibiotics. The carbapenem group displayed a significant loss of microbial diversity at engraftment and an increased rate of acute GI GvHD (32.1%) compared to the noantibiotics group (11.6%).…”
Section: Antibiotic Treatmentmentioning
confidence: 99%
“…In clinical practice, the traditional preventative treatment including systemic drug bath and negative pressure aseptic laminar flow ward monitoring, both have been widely accepted. However, the prophylactic use of antibiotics is still controversial [9]. In addition, predictive nursing is a new concept proposed in recent years, which refers to the simple way before the occurrence of adverse events to block the initiation of the event, so as to improve the prognosis of patients and reduce the cost of treatment [5].…”
Section: Discussionmentioning
confidence: 99%